Hepatic failure at obstructive parasitogenic cholestasis - V. F. Tskhay; N. A. Brazhnikova; L. M. Paramonova; L. Yu. Petrov (Бюллетень сибирской медицины, 2004)
In Tomsk zonal hepatologic center 358 patients with obstructive parasitogenic jaundice have been operated (alveococcosis-based — 43, echinococcosis-based — 17, opisthorchosis-based — 298). Clinical presentations of hepatic failure before the surgery have been observed at 30,7% of patients, more often — under long and intensive cholestasis. Postsurgical hepatic failure has developed at 23,1%. Intraportal medicine infusions play an important role in prophylaxis and treatment of hepatic failure along with timely and optimal surgery. Infusions permit to decrease the hepatic failure progress probability from 60,6 to 30,5%, probability of suppurative complications from 10,3 to 3,1% and postsurgical lethality from 38,2 to 9,5%.